Rich and poor countries: a study in problems of comparisons of real income - Usher, Dan (London, Institute of Economic Affairs, 1966)
The book deals with some fundamental aspect of the relationship between the poor and the rich countries as they will continue to govern economic relations with the poorer non- OPEC countries (which after all, contain a very high proportion of the people of the old Third World and, and indeed, of mankind as a whole).
Bibliography: p. 41.
aia 25/02/2019
Loans
Keywords: National income; Cost and standard of living; National income; Cost and standard of living; Rich people; Poor